The effect of increased running speed on the magnitude of impact shock attenuation during ground contact - Ryu, J. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study was to investigate the effect of increased running speed on the magnitude of impact shock attenuation in high frequency (9~20 Hz) at support phase on the treadmill running. Method: Twenty-four healthy male heel-toe runners participated in this study. Average age, height, mass, and preference running speed were 23.43±3.78 years, 176.44±3.38 cm, 71.05±9.04 kg, and 3.0±0.5 m/s, respectively. Three triaxial accelerometer (Noraxon, USA) were mounted to the tuberosity of tibia, PSIS (postero-superior iliac spine), and forehead to collect acceleration signals, respectively. Accelerations were collected for 20 strides at 1,000 Hz during treadmill (Bertec, USA) running at speed of 2.5, 3.0, 3.5, and 4.0 m/s. Power Spectrum Density (PSD) of three acceleration signals was calculated to use in transfer function describing the gain and attenuation of impact shock between the tibia and PSIS, and forehead. One-way ANOVA were performed to compare magnitude of shock attenuation between and within running speeds. The alpha level for all statistical tests was .05. Results: No significant differences resulted for magnitude of the vertical and resultant impact shock attenuation between the tibia and PSIS, and forehead between running speeds. However, significant differences within running speed were found in magnitude of the vertical shock attenuation between tibia and PSIS, tibia and forehead at speed of 2.5, 3.0 m/s, respectively. Conclusion: In conclusion, it might be conjectured that muscles covering the knee and ankle joints and shoe's heel pad need to strengthen to keep the lower extremities from injuries by impact shock at relatively fast running speed that faster than preferred running speed.